Visual C# 2005 Recipes A Problem-Solution Approach - Jones, Allen (Apress, 2013)
This book is based on content previously published in theC# Programmer’s Cookbook (Microsoft Press, 2004). All such content has been revised and updated for inclusion in this book. Whereas the C# Programmer’s Cookbook targeted version 1.1 of the .NET Framework, Visual C# 2005 Recipes focuses on .NET Framework 2.0 and C# 2005. In many cases, you will find the recipes in this book still work on .NET Framework 1.1, except for those recipes that use features new to .NET Framework 2.0. In such cases, the recipe highlights the new .NET Framework 2.0 features being used and presents possible alternatives for those using .NET Framework 1.1. x